Determinants of prices increase of agricultural commodities in a global context1 - Borychowski Michał; Czyżewski Andrzej (Management)
The main objective of this article is to present the determinants of increase in agricultural commodity prices after 2006. The other specific aim is to show the factors affecting agricultural raw materials and food prices in the global context. This article is a review paper of the determinants of recent commodity and food prices spikes. However, it provides an outlook on these determinants that were the most important for the increases in the last decade. The last part of the article (conclusions) to some extent is a synthesis of considerations and includes the authors’ opinions concerning determinants and an attempt to identify which ones were the most important in the growth of agricultural commodity prices. These increases in agricultural commodity prices resulted from many factors and it is very difficult to separate the individual impact of each of them, because they occurred in parallel. However, it is possible to indicate several main reasons for these price increases, which are: adverse changes in supply-demand relations in agricultural markets, increases in oil prices (and increases of the volatility of those prices), development of biofuel production from agricultural commodities (the first generation biofuels), dollar depreciation, an increase in operations of a speculative nature on commodity markets and improper economic policy that created an environment for the growth of prices of agricultural products.